CONCEPTUALIZATION OF THE CONCEPT INSTITUTE OF THE MARKET OF INSURANCE SERVICES BASED ON THE NEO-CLASSIC ECONOMY - Klapkiv , Yu. M. (The actual problems of regional economy development, 2017)
The article explores the issues related to the institutional and financial infrastructure based on the scientific achievements of the neoclassical economy. The specific features of the concept of “institutionalization” are substantiated. The initial interpretation of the interpretation of institutions is revealed. Conceptual approaches to the study of the concept of “institutionalization” and “institute” in the insurance services market are defined. The attention to the galaxy values provided by the notion of an institution or organization.